2018
DOI: 10.3390/molecules23112949
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antioxidant Characteristic of Traditional and Industrial Zhenjiang Aromatic Vinegars during the Aging Process

Abstract: Zhenjiang aromatic vinegar (ZAV) is one of the well-known fermented condiments in China, which is produced by solid-state fermentation. It can be classified into traditional Zhenjiang aromatic vinegar (TZAV) and industrial Zhenjiang aromatic vinegar (IZAV) because of different production methods. The purpose of the study was to evaluate the variations and differences on chemical compositions and antioxidant activities of TZAV and IZAV during the aging process. The proximate composition, organic acids content, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 67 publications
(68 reference statements)
2
46
0
Order By: Relevance
“…Raw materials of ZAV include rice, wheat bran and rice hulls. The brewing process of ZAV is mainly divided into five stages: alcoholic fermentation (AF), acetic acid fermentation (AAF), leaching, decoction and aging stage [5]. During the process, it produces many chemical compositions such as organic acids, amino acids, sugars and other bioactive compounds, which have benefit effects on human health [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Raw materials of ZAV include rice, wheat bran and rice hulls. The brewing process of ZAV is mainly divided into five stages: alcoholic fermentation (AF), acetic acid fermentation (AAF), leaching, decoction and aging stage [5]. During the process, it produces many chemical compositions such as organic acids, amino acids, sugars and other bioactive compounds, which have benefit effects on human health [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies [1,3,4,26,27] provided complex and diverse results on the same topic. The determined compounds have different characteristics, geometry and symmetry.…”
Section: Resultsmentioning
confidence: 99%
“…Plants (fruits, vegetables, herbs, etc.) contain a wide variety of free radical scavenging molecules such as phenolic compounds (e.g., phenolic acids, flavonoids, quinones), nitrogen compounds (e.g., alkaloids, amines), vitamins and terpenoids [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…accurate formulation for aromatic vinegar, it has a hundred years of mature, reliable production technology and quality control. What's more, Chinese literature has found that Hengshun aromatic vinegar contains 88.09% water and volatile matter and 11.91% solid matter (w/v), and is rich in organic acids, sugar, protein, amino acids and other aromatic ingredients, which largely affect its taste characteristics and organoleptic quality (Zhao et al, 2018). The effective components in it are relatively abundant and stable through the fingerprint analysis and amino acid analysis.…”
Section: Discussionmentioning
confidence: 99%
“…During the brewing process, aromatic vinegar produces many bioactive compounds, such as organic acids, amino acids and phenolic compounds, which play important roles in antioxidant activities (Zhang et al, 2019). In addition, polyphenols, flavonoids, and melanoidins were found in Hengshun aromatic vinegar, which play crucial roles in diseases prevention and contribute benefits to human health (Zhao et al, 2018;Duan et al, 2019). Studies have also showed that the alkylpyrazine named ligustrazine was found as a bioactive compound in Hengshun aromatic vinegar, which has the health effects such as reducing blood pressure, promoting blood circulation and removing stasis, improving coronary heart disease, thrombolytic therapy and liver protection (Xu et al, 2011b;Chen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%